Digital Competences and Artificial Intelligence in Higher Education: Systematic Review Article - Egusquiza, Raúl Cortez; Montenegro, Luz Petronila Blas; Chávez, José Antonio Manco; Poma, Amparo Argüelles Romero de; Castellanos, José Alberto Paredes; Paredes, Dora Julia Briceño de; Rivera, Pedro Ricardo Infantes (International Journal of Membrane Science and Technology, 2023)
It is observed that students and professors of the different existing universities in the world have the technological tools that would allow them to continuously carry out an education strengthened by the appropriate platforms with the necessary information to answer multiple questions and tasks, this research is a work of systematic review article. The method used was PRISMA, a very meticulous and rigorous written method performed in the structure for the construction of the research, the search for information was carried out in the following databases such as Scopus, Redalyc, SproQues, SciELO, obtaining 898,276 articles or academic papers in the entire search, excluding 898,218 and considering only 58 academic papers that were selected for the research; according to the academic works carried out in 10 years, the results shown an increasing way from year 2014 to 2023, showing a big change in 2021 corresponding to the use of the tools being more frequently in students of all educational levels, due to quarantines established by governments, being them the technological tools for a synchronous virtual education; digital skills are increasingly essential in today’s labor market. Owning these skills increases employability and career opportunities. In education, digital competences enable students to access to online learning resources, collaborate on digital projects, and adapt to online education environments. Digital competences facilitate online communication and collaboration, which is crucial in a globalized and connected world.